Why does unemployment differ for immigrants? - Stephen Drinkwater (IZA World of Labor, 2017)
The adverse effects of unemployment are a cause for concern for all demographic groups but they will be most acute for those experiencing the highest unemployment rates. In particular, high levels of unemployment are observed for a range of immigrant groups across many countries. However, there is considerable variation both across and within countries. It is therefore important to determine the factors that are most likely to cause high rates of unemployment, especially from a migration perspective, and to identify appropriate policy responses (e.g. enhancing human capital and improving job search effectiveness).
Keywords: J6; J24; 330; unemployment; immigrants; human capital